Peran Lingkungan Pesantren Amindy Barokah Dalam Meningkatkan Kemandirian Belajar Santri - Ainul Mardiyah; Rafif Alwan Najib; M. Amirun Mukhlis; Aldi Arianto Maulana (CV. SINAR HOWUHOWU, 2026)
Learning independence is one of the important competencies that students must have when undergoing education at Islamic boarding schools. The Islamic boarding school environment is not only a place for the transfer of knowledge, but also a means of forming character, discipline and responsibility. This research aims to find out how the Amindy Barokah Islamic Boarding School environment increases students' learning independence through learning habits, time management, and spiritual formation. The research uses a descriptive qualitative approach with data collection techniques through interviews and observation. The results of the research show that students' learning independence is formed from the start of their boarding school, they are accustomed to it through a strict schedule, learning activities outside formal hours, the example of the ustadz, and guidance to face the challenges of adolescence. Santri also show high initiative when facing learning difficulties. Thus, the Islamic boarding school environment has a significant role in creating students who are independent and responsible in learning.